Implementation of Dispute Resolution Through Mediation in Civil Cases of Land Ownership Disputes Based on Supreme Court Regulation Number 1 of 2016 concerning Mediation - Zulfi Diane Zaini; Shafana Amalia Azahra (CV. Rayyan Dwi Bharata, 2024)
Land ownership rights in Law Number 5 of 1960 concerning Basic Regulations on Agrarian Principles are included in the concept of primary land rights. Primary land rights mean rights to land that can be owned or controlled directly by a person or legal entity for a long period of time and can be transferred to other people or their heirs. The problem in this research is regarding how to implement dispute resolution through mediation based on PERMA Number 1 of 2016 concerning Mediation and what the legal force of a Deed of Peace is for both parties in land ownership disputes based on PERMA Number 1 of 2016 concerning Mediation. The research method used in this research is a normative juridical approach and an empirical approach. Secondary data is data obtained through library research, such as literature books and scientific works related to research problems. Secondary data consists of 3 (three) Legal Materials, namely, Primary, Secondary and Tertiary Legal Materials. Prime data is data obtained from research results in the field directly on research objects (field research) carried out by means of direct observation and interviews. The results of this research show that the Tanjungkarang Class 1 A District Court has implemented dispute resolution which is handled by every judge who is obliged to make an offer or peace to both parties in the dispute. If the case examining judge does not order mediation first then it is considered to have violated the law regarding Mediation in the Courts and the Supreme Court with an interim decision will order the Court of First Instance to carry out the Mediation Process, with the time limit given for the interim decision starting from 30 days after notification of the interim decision of the High Court or Supreme Court. The Legal Strength of the Deed of Peace for both parties in a Land Ownership Dispute Based on PERMA Number 1 of 2016 concerning Mediation, has the same strength as that which has permanent and final legal force because it cannot be appealed, cassation or judicial review and has executorial power for the Parties.